2020
DOI: 10.1111/jpn.13314
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the miRNA transcriptome of Rongchang pig longissimus dorsi at weaning and slaughter time points

Abstract: MicroRNA (miRNA) is essential for the process of gene posttranscriptional regulation in skeletal muscle of many species, such as mice, cattle and so on. However, a little number of miRNAs have been reported in the muscle development of Chinese native pig breeds. In this study, the longissimus dorsi transcripts of Chinese native Rongchang pig at weaning and slaughter time points were analysed for miRNA‐seq. The results showed that 19 novel and 186 known miRNAs involved in the Rongchang pig skeletal muscle devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Overexpression of miR-22-3p promotes myoblast differentiation and reduces proliferation in mouse myoblasts ( Marzi et al, 2012 ). Similar results were seen in porcine satellite cells ( Chen et al, 2020 ). miR-127 plus others have been selected for further testing as important miRNA and their potential role in muscle development and meat quality ( Iqbal et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overexpression of miR-22-3p promotes myoblast differentiation and reduces proliferation in mouse myoblasts ( Marzi et al, 2012 ). Similar results were seen in porcine satellite cells ( Chen et al, 2020 ). miR-127 plus others have been selected for further testing as important miRNA and their potential role in muscle development and meat quality ( Iqbal et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…miR-29 was found in muscle and satellite cell cultures, however satellite cell cultures had higher abundance of the miRNA. Postnatally miR-29a was found to be upregulated and miR-127 was down regulated from weaning to maturity in pigs ( Chen et al, 2020 ). A similar trend with miR-29a was found in the current study, however miR-127 was only down regulated during the prenatal to early postnatal comparisons (PN2 vs. PN3, PN3 vs. PW1, and PW1 vs. PW2).…”
Section: Discussionmentioning
confidence: 99%
“…Four down-regulated known caprine miRNAs (miR-127-3p, miR-217-5p, miR-410-3p, and miR-487b-3p) in LC goats attracted our attention. The miR-127-3p has been reported to inhibit proliferation of C2C12 myoblast ( 50 ), as well as proliferation and differentiation of porcine skeletal muscle satellite cells ( 51 ). Similarly, miR-217-5p and miR-487b-3p inhibited the differentiation of skeletal muscle cells in rats ( 52 ) and mice ( 53 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs which playing significant roles in skeletal muscle development could be used as biomarkers after further validation. Further, the authors also reported that miR-217 could act as an inhibitor of porcine satellite cells (PSCs) proliferation and differentiation through downregulating the expression of cyclin B, cyclin D, as well as proliferating cell nuclear antigen (PCNA) and MyoG and MyHC respec-tively [61]. Remarkably, miR-208b and miR-499 are responsible for the transcriptional repression of the slow-twitch protein gene SRY-box transcription factor 6 (Sox6).…”
Section: Role Of Mirnas In Myogenesismentioning
confidence: 99%
“…Other miRNAs involved in porcine skeletal muscle development include miRNA-21, a novel myogenic miRNA that regulates skeletal muscle development through controlling the Pphosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling by targeting the transforming growth factor-β I (TGFβI) gene [18]. In PSCs in skeletal muscle miR-22 inhibits the proliferation through targeting the cyclin D1, cyclin B1, and p21 but promotes the differentiation through regulating the expression of MyoG and MyHC [61]. Further, miR-27a inhibits the expression of MyoG and it also regulates the protein kinase B/forkhead box protein O1 (Akt/FoxO1) signal pathway during porcine myogenesis [75] while miR27b acts to promote PSCs myogenesis by targeting MyoD family inhibitor (MDFI) [76].…”
Section: Role Of Mirnas In Myogenesismentioning
confidence: 99%